2008
DOI: 10.1029/2007gc001917
|View full text |Cite
|
Sign up to set email alerts
|

Long‐term tilt and acceleration data from the Logatchev Hydrothermal Vent Field, Mid‐Atlantic Ridge, measured by the Bremen Ocean Bottom Tiltmeter

Abstract: [1] Long-term seafloor deformations in the Logatchev Hydrothermal Vent Field (LHF) at the Mid-Atlantic Ridge are largely unexplored and unknown, even though the LHF has been the focus of international research for many years. As seafloor tilt and vertical acceleration provide key information about seafloor deformations, the Bremen Ocean Bottom Tiltmeter (OBT) was deployed in May 2005 at position 14°45 0 11.7 00 N, 44°58 0 47.0 00 W, 3035 m water depth in the LHF. The OBT recorded 384 days and was recovered in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
2

Year Published

2009
2009
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 21 publications
(12 citation statements)
references
References 34 publications
1
7
2
Order By: Relevance
“…Tilt cycles with similar periods have been observed near the Logatchev hydrothermal field on the MAR at 14°45 0 N [Fabian and Villinger, 2008], and when combined with our bottom pressure data, these observations provide compelling evidence for regular, hydrothermal flow-induced, GSD cycles at deep-sea hydrothermal fields.…”
Section: Discussionsupporting
confidence: 52%
“…Tilt cycles with similar periods have been observed near the Logatchev hydrothermal field on the MAR at 14°45 0 N [Fabian and Villinger, 2008], and when combined with our bottom pressure data, these observations provide compelling evidence for regular, hydrothermal flow-induced, GSD cycles at deep-sea hydrothermal fields.…”
Section: Discussionsupporting
confidence: 52%
“…These might reflect internal wave activity. In contrast to the observations of Fabian and Villinger [2008] and of Sohn et al…”
Section: Medium-term Variationcontrasting
confidence: 55%
“…Pressure probe data for the TAG hydrothermal field shows periodic ground deformation that have been interpreted with a geyser‐like mechanism [ Sohn et al , 2009], yet TAG presents no craters. Tilt cycles with similar periods as those described at TAG by Sohn et al [2009] have been measured at the Logatchev field [ Fabian and Villinger , 2008]. These authors suggested that pressure fluctuations occur in the hydrothermal upflow zone with a periodicity comparable to those measured near on‐land geysers [ Nishimura et al , 2006].…”
Section: Discussionmentioning
confidence: 99%